Younger than springtime - Greeley, Andrew M., 1928- (New York : Forge, 1999)
Charles "Chucky" O'Malley arrives in Chicago following a chaotic tour in postwar Germany to get an accounting degree, but Father Pius is determined to expel him.
"A Tom Doherty Associates book."
Keywords: Irish Americans -- Illinois -- Chicago -- Fiction; Chicago (Ill.) -- Fiction; Domestic fiction